Investigation of the Scanning Microarc Oxidation Process - Lingqin Xia; Jianmin Han; Joseph P. Domblesky; Zhiyong Yang; Weijing Li (Advances in Materials Science and Engineering)
Scanning microarc oxidation (SMAO) is a coating process which is based on conventional microarc oxidation (MAO). The key difference is that deposition in SMAO is achieved by using a stainless steel nozzle to spray an electrolyte stream on the substrate surface as opposed to immersing the workpiece in an electrolyzer. In the present study, SMAO discharge characteristics, coating morphology, and properties are analyzed and compared to results obtained from MAO under similar conditions. Results show that MAO and SMAO have comparable spark and microarc lifetimes and sizes, though significant differences in incubation time and discharge distribution were evident. Results also showed that the voltage and current density for MAO and SMAO demonstrate similar behavior but have markedly different transient and steady-state values. Results obtained from coating A356 aluminum sheet show that oxide thickness and growth rate in SMAO are strongly dependent on interelectrode spacing and travel speed. Analysis of the SMAO coating morphology and structure showed that a denser and slightly harder layer was deposited in comparison to MAO and is attributed to reduced porosity and increased formation of α-Al2O3. Preliminary results indicate that SMAO represents a viable process for coating of aluminum surfaces.